Prevalence of Girl Child Abuse in Kerala: An Analysis - Lima Raj, K & Manikandan, K (Guru Journal of Behavioral and Social Sciences, 2013)
This study is an attempt to analyze the prevalence of girl child abuse in Kerala. News papers of three national dailies and Crime Records Bureau sites of Kerala (SCRB) and India (NCRB) were referred for the purpose of obtaining relevant data. It was found that there is an alarming rate of increase in the sexual abuse of girl children in Kerala. Based on the available information from the above media the study also tried to examine the details of the victim, the abuser/offender and news paper reports. A great majority of children who are exposed to sexual abuse are done so by someone they know -father, brother, uncle, male teacher etc. From the reported cases it has to be noted that sexual abuse manifestations occurred at two levels mainly- home and institutional level. The findings of the study are discussed in detail.